2010
DOI: 10.1111/j.1460-9592.2010.03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the newer preparation of propofol, an emulsion of medium/long chain triglycerides cause less injection pain in children when premixed with lignocaine?

Abstract: Propofol MCT/LCT and propofol LCT premixed with lignocaine are both associated with pain on injection in children; the incidence and intensity of the injection pain are similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Varghese et. al ., on the other hand, found no difference in the incidence or severity of injection pain when lidocaine is added to both MCT/LCT propofol and LCT propofol [160]. A systematic review and meta-analysis recommends that the use of a small dose of opioids before induction of anesthesia and to use an antecubital vein instead of a hand vein for the propofol lidocaine admixture administration is a simple and effective way to avoid pain.…”
Section: ) Adverse Effectsmentioning
confidence: 99%
“…Varghese et. al ., on the other hand, found no difference in the incidence or severity of injection pain when lidocaine is added to both MCT/LCT propofol and LCT propofol [160]. A systematic review and meta-analysis recommends that the use of a small dose of opioids before induction of anesthesia and to use an antecubital vein instead of a hand vein for the propofol lidocaine admixture administration is a simple and effective way to avoid pain.…”
Section: ) Adverse Effectsmentioning
confidence: 99%
“…[16,17] Propofol-LCT/MCT was specially proposed to decrease injection pain. Varghese et al [18] reported that when added with lidocaine, both propofol-LCT/MCT and propofol-LCT had similar incidence of injection pain. By a systemic review and meta-analysis in 2011, pretreatment with a small dose of opioids halved the incidence of pain after propofol injection, which can generally be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9,17] In the previous study, when premixed with lignocaine, there was no difference in the incidence of pain between propofol LCT and propofol LCT/MCT. [17] …”
Section: Discussionmentioning
confidence: 99%